An Overview of Employees2019; Dynamic Capabilities, Job Performance with Innovative Work Behaviour: A Conceptual Paper (Global Journal of Management and Business Research, 2020)
This paper focuses on the theoretical review of employees dynamic capabilities innovative work behavior and job performance It also determines the mediating role of innovative work behavior on the nexus between employees dynamic capabilities and job performance Dynamic capabilities become a fundamental source of competitive advantage through the mediating role of innovative work behavior The review of previous studies indicates that the dynamic capabilities of employees have not studies indicates that as a distinct subject